Reconfigurable Electro-optic Logic Circuits Using Microring Resonator-Based Optical Switch Array - Yonghui Tian; Guolin Zhao; Zilong Liu; Anqi Guo; Huifu Xiao; Xiaosuo Wu; Yinghao Meng; Lin Deng; Xiaonan Guo; Guipeng Liu; Jianhong Yang (IEEE Photonics Journal, 2016)
In this paper, we propose a reconfigurable electro-optic logic circuit, which can perform any combinatorial logic operations using a microring resonator (MRR)-based optical switching array. The operands are represented by electrical signals, which are applied to the corresponding MRRs to control their switching status. The operation results are directed to the output port in the form of light. For proof of concept, the circuit consisting of four thermooptic MRR-based optical switches is fabricated on the silicon-on-insulator (SOI) substrate using the commercial complementary metal–oxide–semiconductor (CMOS) fabrication process. Finally, several logic operations of four operands with the operation speed of 10 kb/s are demonstrated successfully.